Adults with metabolically healthy overweight or obesity present more brown adipose tissue and higher thermogenesis than their metabolically unhealthy counterparts - Jurado-Fasoli, Lucas (Elsevier, 2025)
Background There is a subset of individuals with overweight/obesity characterized by a lower risk of cardiometabolic complications, the so-called metabolically healthy overweight/obesity (MHOO) phenotype. Despite the relatively higher levels of subcutaneous adipose tissue and lower visceral adipose tissue observed in individuals with MHOO than individuals with metabolically unhealthy overweight/obesity (MUOO), little is known about the differences in brown adipose tissue (BAT).
Methods This study included 53 young adults (28 women) with a body mass index (BMI) ≥25 kg/m2 which were classified as MHOO (n = 34) or MUOO (n = 19). BAT was assessed through a static 18F-FDG positron emission tomography/computed tomography scan after a 2-h personalized cooling protocol. Energy expenditure, skin temperature, and thermal perception were assessed during a standardized mixed meal test (3.5 h) and a 1-h personalized cold exposure. Body composition was assessed by dual-energy x-ray absorptiometry, energy intake was determined during an ad libitum meal test and dietary recalls, and physical activity levels were determined by a wrist-worn accelerometer.
Findings Participants with MHOO presented higher BAT volume (+124%, P = 0.008), SUVmean (+63%, P = 0.001), and SUVpeak (+133%, P = 0.003) than MUOO, despite having similar BAT mean radiodensity (P = 0.354). In addition, individuals with MHOO exhibited marginally higher meal-induced thermogenesis (P = 0.096) and cold-induced thermogenesis (+158%, P = 0.050). Moreover, MHOO participants showed higher supraclavicular skin temperature than MUOO during the first hour of the postprandial period and during the cold exposure, while no statistically significant differences were observed in other skin temperature parameters. We observed no statistically significant differences between MHOO and MUOO in thermal perception, body composition, outdoor ambient temperature exposure, resting metabolic rate, energy intake, or physical activity levels.
Interpretation Adults with MHOO present higher BAT volume and activity than MUOO. The higher meal- and cold-induced thermogenesis and cold-induced supraclavicular skin temperature are compatible with a higher BAT activity. Overall, these results suggest that BAT presence and activity might be linked to a healthier phenotype in young adults with overweight or obesity. Funding See acknowledgments section.